A correlational study between the volatility of the stock returns and remittances, exports, imports and international reserves: Evidence on the Philippine market - Romero, Frederick P. (Animo Repository, 2017)
The study examines how certain macroeconomic variables influence the movement of the Philippine Stock Exchange Index (PSEi) and to find significance in their relationship. The following macroeconomic variables were used in this study: remittances, export level, import level and the international reserves of the Philippines. Monthly data of these variables and the PSEi prices from the period 2005–2014 have been obtained for the study. To test for the stationary of data, the paper used the Augmented Dickey Fuller (ADF). Moreover, the study opted to use the LaGrange-Multiplier Test of ARCH Test and Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH) to assess the heteroscedasticity of the given variables. Finally, Granger Test for Causality was used to determine and to confirm the long-run dynamic relationship between PSEi and the given economic variables. Empirical findings revealed that remittances, imports, exports and international reserves do not seem to influence the stock returns for the period used. The causality between each of the given macroeconomic variables and the Philippine Stock Exchange index is statistically insignificant. The result of the paper suggests that in the long run, the Philippine stock market is not reactive to the volatility of remittances, import level, export level and international reserves, and the same cannot be used in predicting future stock performance. © 2017 American Scientific Publishers All rights reserved.